PENDAMPINGAN SOCIAL MEDIA PROMOTION (INSTAGRAM) PADA UMKM AJAY FURNITURE BANDAR LAMPUNG - Roni, May; Damayanti, Damayanti; Saptiani, Fenny; Paramita Djausal, Gita (Jurnal Abdimas Bina Bangsa, 2025)
The Social Media Promotion (Instagram) assistance program for Ajay Furniture MSMEs in Bandar Lampung aims to increase the competitiveness and market reach of MSMEs through an effective promotion strategy on the Instagram platform. Instagram, as one of the social media that has high active users, offers great potential for MSMEs to introduce products more widely and attract new customers. In this program, Ajay Furniture MSMEs are accompanied to understand how to optimize the use of Instagram, starting from creating interesting content, account management, using advertising features, to analyzing data for promotion performance evaluation. This assistance is carried out intensively with a direct training approach and periodic consultations to ensure the implementation of sustainable strategies. The results of this program show an increase in Instagram account engagement as well as growth in the number of followers and sales of Ajay Furniture products. This program proves that social media optimization, especially Instagram, can be one of the effective solutions in expanding the market for MSMEs in the digital era